2020
DOI: 10.2298/pif2003145j
|View full text |Cite
|
Sign up to set email alerts
|

Harmonia axyridis (Coleoptera: Coccinellidae) in Serbia: Its presence on aphid-infested plants and co-occurrence with native Aphidophagous coccinellids

Abstract: The presence of the invasive coccinellid Harmonia axyridis in aphid colonies on plants, as well as its co-occurrence with native coccinellid predators was studied in the period 2011-2020. Also, its occurrence on fruit plants and grapes was monitored at harvest time. Research was conducted on 41 locations in Serbia. The feeding of this invasive species was recorded on a total of 43 aphid taxa of 25 different genera. It was most frequently present on aphid colonies of the genera Aphis, Brachyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…in the fruit orchards. Similarly, Jovičić et al (2020) reported that Harmonia axyridis fed on 43 aphid species on 58 cultivated plant species such as ten fruit, seven field crops, five vegetables and 16 ornamental species, as well as 20 non-cultivated plants. In this context, it has been announced that plant volatiles originating from aphid damaged have an important role in guiding prey foraging and in increasing aphid predation rates of H. axyridis, whose host prey aphid number is quite high (Francis et al 2004, Xiu et al 2019.…”
Section: Scymnus Apetzi Mulsant 1846mentioning
confidence: 97%
“…in the fruit orchards. Similarly, Jovičić et al (2020) reported that Harmonia axyridis fed on 43 aphid species on 58 cultivated plant species such as ten fruit, seven field crops, five vegetables and 16 ornamental species, as well as 20 non-cultivated plants. In this context, it has been announced that plant volatiles originating from aphid damaged have an important role in guiding prey foraging and in increasing aphid predation rates of H. axyridis, whose host prey aphid number is quite high (Francis et al 2004, Xiu et al 2019.…”
Section: Scymnus Apetzi Mulsant 1846mentioning
confidence: 97%